Activating peroxymonosulfate by N and O co-doped porous carbon for efficient BPA degradation: A re-visit to the removal mechanism and the effects of surface unpaired electrons - He, Yong-Li; He, Chuan-Shu; Lai, Lei-Duo; Zhou, Peng; Zhang, Heng; Li, Ling-Li; Xiong, Zhao-Kun; Mu, Yang; Pan, Zhi-Cheng; Yao, Gang; Lai, Bo (Applied catalysis. B, Environmental, 2022)
In this study, N and O co-doping carbon materials with porous structure (NOPC-x) were applied to activate peroxymonosulfate (PMS) for bisphenol (BPA) degradation and the underlying effects in affecting NOPC-x activity were revealed. Electrochemical characterization, electron paramagnetic resonance (EPR) tests, quenching and PMS adsorption experiments were applied to clarify the mechanism of BPA degradation. It’s found that BPA can be completely removed within 20 min (kobs = 0.30 min−1) in the NOPC/PMS system depending on the electron transfer path with the necessity of moderate surfaced unpaired electrons for electrons delivery, which could be regulated by the modifier dosage. However, excessive surfaced unpaired electrons were unfavorable to PMS adsorption, resulting in deterioration of BPA degradation. This study indicates that controlling the amount of surfaced unpaired electrons in an appropriate range is essential to ensure the carbonaceous materials activity in PMS activation to obtain a satisfactory BPA degradation. [Display omitted] ●NOPC exhibited superior activity for BPA degradation by PMS activation.●Increasing heteroatomic doping enhanced the amount of surfaced unpaired electrons.●Degradation of BPA was proposed to follow a nonradical electron transfer pathway.●The role of surfaced unpaired electrons of NOPC in PMS activation was clarified.